2010
DOI: 10.1016/j.jpainsymman.2009.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Correlation and Interrater Reliability for Four Performance Scales in the Palliative Care Setting

Abstract: Performance scales are used by clinicians to objectively represent a patient's level of function and have been shown to be important predictors of response to therapy and survival. Four different scales are commonly used in the palliative care setting, two of which were specifically developed to more accurately represent this population. It remains unclear which scale is best suited for this setting. The objectives of this study were to determine the correlations among the four scales and concurrently compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 31 publications
1
37
0
1
Order By: Relevance
“…Thus, this study provides a useful means of converting between the CFS and PPS, regardless of diagnosis or care setting. In addition, previous studies assessing conversion between performance scales have used the same rater (a physician) to score both scales . The current study used four raters for each participant; a physician and a nurse from the respective specialty completed each scale so that clinicians who would most likely be using them in clinical practice completed the scales and to avoid bias that might result from the same rater completing both measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this study provides a useful means of converting between the CFS and PPS, regardless of diagnosis or care setting. In addition, previous studies assessing conversion between performance scales have used the same rater (a physician) to score both scales . The current study used four raters for each participant; a physician and a nurse from the respective specialty completed each scale so that clinicians who would most likely be using them in clinical practice completed the scales and to avoid bias that might result from the same rater completing both measures.…”
Section: Discussionmentioning
confidence: 99%
“…These scales identify an individual's burden of illness, enabling clinicians to plan the course of treatment, select appropriate interventions, and determine eligibility for clinical trials . The allocation of healthcare resources in nursing homes, home care services, hospices, and palliative care units may be based on performance scale scores . These scales also allow professionals in each medical specialty to communicate efficiently about individuals' functional status using a common language.…”
mentioning
confidence: 99%
“…Although these scales are widely used in the clinical decision-making process in practice and research settings, information on inter-observer agreement is scarce and mostly dates from the 1980s. Regarding the rates of absolute agreement between the raters, recent papers have reported contradictory findings [ 1 , 9 ]. Moderate to high concordance rates were found for KPS (63–75 %) and ECOG PS (90–92 %) in a study that included patients with better-functioning scores [ 1 ]; however, another study [ 9 ] found low absolute agreement rates in a palliative care setting (ECOG PS = 53–61 %; KPS = 38–50 %).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the rates of absolute agreement between the raters, recent papers have reported contradictory findings [ 1 , 9 ]. Moderate to high concordance rates were found for KPS (63–75 %) and ECOG PS (90–92 %) in a study that included patients with better-functioning scores [ 1 ]; however, another study [ 9 ] found low absolute agreement rates in a palliative care setting (ECOG PS = 53–61 %; KPS = 38–50 %). Therefore, there is a need for the development of new valid scales or assessment strategies showing better inter-observer reliability.…”
Section: Introductionmentioning
confidence: 99%
“…A escala Karnofski foi criada em 1940 com a finalidade de identificar a necessidade de indicar Cuidados Paliativos. A escola contem parâmetros que determinam uma classificação geral do desempenho dos pacientes com base no nível de deambulação, atividade e capacidade de realizar o autocuidado(MYERS et al, 2010).A partir da definição da amostra, a equipe de pesquisa realizou reuniões com as equipes locais e a supervisão de saúde de Parelheiros e identificou os usuários que poderiam participar da pesquisa, totalizando ao término da coleta 26 sujeitos.Alguns usuários, em virtude do grau de comprometimento neurológico não puderam responder diretamente ao instrumento de pesquisa. Nesses casos, o entrevistado foi o cuidador.…”
unclassified